Harnessing experience-dependent plasticity for CNS repair and regeneration. (September 2012) - Cumming, Toby B; Bernhardt, Julie; Hannan, Anthony J
The 7th World Congress of Neurorehabilitation was held from 16–19 May, 2012, in Melbourne, Australia. Melbourne produced the largest attendance of any meeting thus far for this biennial congress of the World Federation of Neurorehabilitation. The congress provided a diverse range of presentations, from environmental interventions in animal models of brain disorders, to new techniques for rehabilitation and clinical trials. While stroke, traumatic brain injury and spinal cord injury featured prominently, there were also many other presentations on rehabilitation for neurodegenerative diseases and other neurological disorders. Here, we focus on a selection of novel findings reported at this congress.